OVERVIEW OF WHALE RESEARCH IN VIETNAM AND SOME PROTECTION SOLUTIONS - Thuoc, Pham (Vietnam Journal of Marine Science and Technology, 2007)
There were some researches on whale in Vietnam and Southeast Asia seawaters (Perrin 1994, Smith et al., 1995). Fin whale (Balaenoptera physalus) was firstly recognized in Vietnam by Gruvel (1925). There was no specific study focusing on whale in Vietnam seawaters (Smith et al., 1995). Dugong was recorded some times in Vietnam (Tran Ngoc Loi, 1962; Van Bree and Duguy, 1997). In March - April 1995, the first study on whale was carried out in the Central and Southern Vietnam, in Mekong Delta and Phu Quoc Island (Gulf of Thailand). In this study, 17 whale species were described. Another similar study was made in the Gulf of Tonkin in October 1999 and April 2000 and still using the observation method, in this study 10 whale species were identified. The two series of studies mentioned above were carried out by IUCN experts in whale and Ocean Park Conservation Foundation and Vietnamese experts from some institutions, and 6 more whale species were recorded. In all, 25 species of Cetaceans are recognized in the Vietnamese seawaters. Based on studies and historical references, it is considered that whales have no great economic value but have a great spiritual significance for the fisherfolk in Vietnam, especially in the Central and Southern Vietnam. Whales are respected and worshiped. Whales are worshiped in annually festival days. Fishermen call whales “Ca Ong Voi” (Vietnamese) or Mister Ong. Legend said that Ca Ong Voi saves fisherman and its friends from storms and tempests using its body to prop boats/vessels or fellow-creatures in distress at sea. Fisherfolk have built temples to worship Ca Ong Voi so as to express their great gratitude and respect. In addition, there are some stories of the intelligence of Ca Ong Voi (especially dolphin species of the toothed whales (suborder Odontoceti)) and the good relationship between whale in general and dolphin in particular with man. The Central and Southern Vietnam have many Ca Ong Voi temples keeping skeletons of whale and other mammals like Dugong and dolphin, which are very valuable to research activities. Fin whale is a fish species of internal fecundation like various terrestrial mammal species. The female remain pregnant for 11 months before giving birth. Right after being born, the calf instinctively swims to the surface. In the first days, the newborn always stay closely with the mother. The calf is nurtured with its mother’s milk and is weaned in 7 months. Calves reach sexual maturity in 6 - 7 years. Fin whale distribute mainly in temperate seawaters. In the winter, they migrate toward the south, into warmer waters to feed, and in the spring they migrate back. The South China Sea (Eastern Sea) is also a feeding area of various toothless whales. When feeding, some whale individuals died due to hanging up against fishing net or certain reasons, and were washed onto the shore. The people living at the coastal villages buried dead whales kindly and built temples to worship them as the Sea Deity, because legend said that whale (Ca Ong Voi) rescued persons in distress from waves and storms in the ocean.